Evaluasi Penggunaan Formula Bumbu Penyedap Berbasis Jamur Tiram pada Sistem Penyelenggaraan Makanan - Kadaryati, Sri; Afriani, Yuni; Yolin, Jessika (Jurnal Gizi, 2022)
Formula development and sensory evaluation of seasoning agents using oyster mushroom has been carried out in the previous studies. Sensory quality is a food quality parameter that affectednutritional fulfillment and satisfaction. The use of seasoning agents was needed to be evaluated on foodservice system as a sensory evaluation in large quantities of processing. The objectives of this study wereto determine differences in food satisfaction and nutritional fulfillment on food service using seasoningagent of oyster mushroom. This was quasi-experimental study, conducted in July 2019 at Sekolah AlamNurul Islam, Yogyakarta. Respondents were the teachers. Data on nutritional needs were calculated usingweight and height, whereas food intake was obtained using food recall. Data of food recalls wereanalyzed using Nutrisurvey to obtain energy, protein, fat, and carbohydrate intake. Furthermore,nutritional fulfillment was obtained by comparing the food intake with the nutritional needs. Foodsatisfaction was obtained by interview using a food satisfaction questionnaire. Data were analyzed usingWilcoxon Test and Chi Square Test. The results showed that there were no differences in nutritionalfulfillment and satisfaction on the first and second days (p>0.05), except for the fulfillment of fat (p<0.05).The differences were found on the third day (p<0.05). Seasoning agents using oyster mushrooms haven’tfully increased food satisfaction and nutritional fulfillment in the food service. The effect still depends onthe type of dish that is processed. Seasoning agent using oyster mushroom still requires formuladevelopment so that it can be applied to dishes processing in food service.Keywords: food intake, seasoning agent, oyster mushroom, food satisfaction, food service